Investigating the Antecedents of Investment Intention and the Mediating Effect of Investment Self-efficacy among Young Adults in Shandong, China - Lim, Thien Sang; Qi, Peng Cheng (People and Global Business Association, 2023)
Purpose: This study examines the antecedents and predictors of investment intention and the mediating role of investment self-efficacy. The study empirically investigates the complexity of the decision-making process related to financial investment in Shandong, China. Design/methodology/approach: The Integrated Behavioral Model underpinned the research. The sample was selected using the judgmental-sampling method. A sample of 313 responses from young income earners aged 25 to 39 was analyzed. Twelve hypotheses were tested using the SmartPLS statistical software. Findings: The resultant outcomes contradict the normative theory of finance. The findings revealed that psychological (risk perception and subjective financial knowledge) and sociological (influences of family, friends, and Internet) factors significantly influence the attitude of young income earners toward investment. Investment self-efficacy demonstrates a significant mediating role, as the indirect effect is almost half the total effect. Evidently, subjective financial knowledge positively influences investment self-efficacy, which in turn has a positive influence on investment intent. Research limitations/implications: The result is concerning as young wage earners appear overconfident in their financial skills. Policymakers and relevant market actors should strive to improve real financial knowledge, as real financial knowledge is known to be linked with the effectiveness of financial investments. Future research in this area may adopt a mixed-method approach as it has the potential to uncover new variables and provide a broader spectrum to understand the complexity of people's investment decision-making process. Originality/value: The study highlights the complexity of the decision-making process. It highlights the central role of self-efficacy in explaining investment intention. The empirical evidence from the world's most populous nation, China, expands the relevance of behavioral finance theory in mainstream finance research.